Reconstructing the Evidentiary Framework for the Annulment of Arbitral Awards to Ensure Legal Certainty - Mohamad Toha Hasan; Chairul Lutfi; Bintan Dzumirroh Ariny (Institut Agama Islam Negeri Ponorogo, 2026)
Article 70 of Law Number 30 of 1999 on Arbitration and Alternative Dispute Resolution permits the annulment of an arbitral award on three specified grounds. Following Constitutional Court Decision Number 15/PUU-XII/2014, the elucidation requiring those grounds to be proven by a prior court judgment ceased to have binding force. Nevertheless, judicial decisions continue to diverge regarding the requirement of a prior criminal judgment. This normative legal study applies statutory, case, and conceptual approaches to South Jakarta District Court Decision Number 427/Pdt. Sus-Arbt/2021/PN JKT.SEL and Number 582/Pdt. Sus-Arbt/2021/PN Jkt.Sel in conjunction with Supreme Court Decision Number 244 B/Pdt. Sus-Arbt/2022, as well as the Central Jakarta District Court Decision Number 699/Pdt. G/2019/PN Jkt.Pst in conjunction with Supreme Court Decision No. 327 B/Pdt. Sus-Arbt/2021. The study finds a divergence between the criminal-judgment prerequisite and direct proof in annulment proceedings. It proposes a five-part evidentiary model: a specific allegation supported by initial evidence; allocation of the burden of proof to the applicant; differentiated proof for each ground in Article 70; prohibition on re-examining the merits of the arbitral dispute; and express judicial reasoning linking the proven procedural defect to the award. Statutory clarification and harmonization of Supreme Court guidance are necessary to improve legal certainty while preserving arbitration’s finality.